Social Paradigms Shaping Leisure Research Designs: A Systematic Review - Tennur Yerlisu Lapa; Elif Köse; İlhan Günbayı (Selcuk University, 2021)
Researchers conduct their studies in accordance with their perspective and philosophy that they ground on. There are philosophical hypothesis and specific beliefs that guide them to define and understand the underlying reasons of a case. These philosophical hypotheses stand out in every stage of the research including conducting the theory, type and method of the research and reporting. The purpose of this study is to review leisure studies in Turkey systematically in the context of paradigms and enlighten historical process of paradigms in the research. Document analyses are used as data collection technique. In accordance with the purpose of this study, literature review is performed in three data bases by using 9 keywords in Turkish and English in total 134 articles are evaluated based on both abstract and full review. It is detected that historical process of leisure studies accompanied by quantitative researches, but qualitative and mix type researches taken place in literature after 2010. Functional Paradigm is dominated when research types are embraced, and survey researches performed more in the Functionalist Paradigm. Institutions providing recreation education are also recommended to support qualitative and mixed method research in order for current approaches in the field to be followed and qualified studies to be put forth.